Comparative analysis of aerobic exercise protocols on depression in post-myocardial infarction rehabilitation - Jawaid, Muhammad; Saeed, Hina; Hasan, Sobia; Perwaiz, Saadia; Basit, Aasma; Lohana, Nisha (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Depression is common among patients recovering from myocardial infarction (MI) and is reportedly associated with poor outcomes. Aerobic exercise has been proposed as a beneficial intervention for improving both cardiovascular health and mental well-being. This study investigated the effects of different aerobic exercise protocols on depressive symptoms in MI patients during their recovery and determine the most effective approach. A randomized controlled trial design was employed, enrolling 120 patients recovering from MI. Participants were randomly assigned to one of the three exercise groups: low-intensity aerobic exercise, moderate-intensity aerobic exercise, and high-intensity interval training (HIIT). Depressive symptoms were assessed using the Beck Depression Inventory (BDI) at baseline, 6 weeks, and 12 weeks post-intervention. Exercise adherence and safety were monitored throughout the study. Significant reductions in depressive symptoms were observed in all exercise groups, with the HIIT interval training group showing the greatest improvement in depression scores compared to the low and moderate-intensity groups. Exercise adherence rates were highest in the moderate-intensity group, while HIIT demonstrated the most significant physiological improvements in cardiovascular fitness. Aerobic exercise, particularly high-intensity interval training, appears to be an effective intervention for reducing depressive symptoms in patients recovering from myocardial infarction. These findings suggest that incorporating structured aerobic exercise into recovery programs may enhance both psychological and physical health outcomes.